Strategic Planning for Green Logistics Implementation in Potato Agro-Industry - Yusianto, Rindra; Marimin, Marimin; Suprihatin, Suprihatin; Hardjomidjojo, Hartrisari (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 6 No 1 (2021)DO - 10.24843/JITPA.2021.v06.i01.p02, 2021)
Indonesia is the largest potato producer in Southeast Asia. Annual production averaged 1.09 million tons. However, productivity is still low, ranging from 16.4 - 18.22 tons/ha. The objective of this study was to propose a strategic planning of the Green Logistic Distribution Center (GLDC) in the potato agro-industry using Interpretative Structure Modeling (ISM). A contribution of this research was that we used ISM to analyze the sustainability policy of the green logistics program which includes social, economic, and environmental issues. The result showed that the objectives such as availability of raw materials (1), supplier of potato (3), market place (5), traffic transportation (7), economic factor (8), and environmental issue (9) include variable linkages from the system. Every action on these objectives will result in a successful GLDC program, while the lack of attention to these objectives will lead to program failure. In this case, the driver power is large but has little dependence on the program. While the other sub-elements of purpose are categorized as dependent, this is interpreted more as a result of other objective actions. With two forms of information, ISM and DP-D matrix diagrams, the deepening of the GLDC program is made possible to support strategic planning.